Conserved developmental transcriptomes in evolutionarily divergent species - Parikh, Anup (BioMed Central, 2010)
BACKGROUND: Evolutionarily divergent organisms often share developmental anatomies despite vast differences between their genome sequences. The social amoebae Dictyostelium discoideum and Dictyostelium purpureum have similar developmental morphologies although their genomes are as divergent as those of man and jawed fish. RESULTS: Here we show that the anatomical similarities are accompanied by extensive transcriptome conservation. Using RNA sequencing we compared the abundance and developmental regulation of all the transcripts in the two species. In both species, most genes are developmentally regulated and the greatest expression changes occur during the transition from unicellularity to multicellularity. The developmental regulation of transcription is highly conserved between orthologs in the two species. In addition to timing of expression, the level of mRNA production is also conserved between orthologs and is consistent with the intuitive notion that transcript abundance correlates with the amount of protein required. Furthermore, the conservation of transcriptomes extends to cell-type specific expression. CONCLUSIONS: These findings suggest that developmental programs are remarkably conserved at the transcriptome level, considering the great evolutionary distance between the genomes. Moreover, this transcriptional conservation may be responsible for the similar developmental anatomies of Dictyostelium discoideum and Dictyostelium purpureum.